Assessment of graduating communication students on call center job - Ledesma-Bautista, Alice Grace (2015.)
The research is about graduating communication students? general assessment on call center jobs. The objectives of the study are to identify the most common channels of information through which graduating communication students learn about call centers, measure graduating communication students? understanding of call center jobs, find out of their common attitude towards call center jobs and determine their possible practice of call center jobs after graduation. This study is grounded on the concepts of Lasswell?s Communication Theory, Berlo?s SMCR Model of Communication, and Social Cognitive Theory emphasizing the purpose of communication, the elements of communication and the different factors that affect people?s decision making. In order to achieve the purpose of the research, a survey form has been made and distributed to chosen respondents, which are graduating communication students from University of the Philippines Visayas and West Visayas State University. The results of the survey, with the help of professional statistician, revealed that graduating communication students are aware of different call center jobs, they have neutral stand with regard to call center jobs, and ultimately, there is a good level of interest among respondents in practicing the job after graduation.
Thesis -- Bachelor of Arts in Communication and Media Studies. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Call Center; Call Center Jobs; Communication Students -- Graduating